Do work factors modify the association between chronic health problems and sickness absence among older employees? - Fenna RM Leijten; Swenne G van den Heuvel; Jan Fekke Ybema; Suzan JW Robroek; Alex Burdorf (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aim of this study was to (i) assess how common chronic health problems and work-related factors predict sickness absence and (ii) explore whether work-related factors modify the effects of health problems on sickness absence. METHODS: A one-year longitudinal study was conducted among employed persons aged 45-64 years from the Study on Transitions in Employment, Ability and Motivation (N=8984). The presence of common chronic health problems and work-related factors was determined at baseline and self-reported sickness absence at one-year follow-up by questionnaire. Multinomial multivariate logistic regression analyses were conducted to assess associations between health, work factors, and sickness absence, and relative excess risk due to interaction (RERI) techniques were used to test effect modification. RESULTS: Common health problems were related to follow-up sickness absence, most strongly to high cumulative sickness absence (>9 days per year). Baseline psychological health problems were strongly related to high sickness absence at follow-up [odds ratio (OR) 3.67, 95% confidence interval (95% CI) 2.80-4.82]. Higher job demands at baseline increased the likelihood of high sickness absence at follow-up among workers with severe headaches [RERI 1.35 (95% CI 0.45-2.25)] and psychological health problems [RERI 3.51 (95% CI 0.67-6.34)] at baseline. Lower autonomy at baseline increased the likelihood of high sickness absence at follow-up among those with musculoskeletal [RERI 0.57 (95% CI 0.05-1.08)], circulatory [RERI 0.82 (95% CI 0.00-1.63)], and psychological health problems [RERI 2.94 (95% CI 0.17-5.70)] at baseline. CONCLUSIONS: Lower autonomy and higher job demands increased the association of an array of common chronic health problems with sickness absence, and thus focus should be placed on altering these factors in order to reduce sickness absence and essentially promote sustainable employability.